Defining the difference: What Makes Biologics Unique - MORROW, THOMAS (BioCommunications LLC, 2004)
Biologics differ from chemically derived drugs in ways that affect their cost, production, administration, and clinical efficacy. Here’s a look at the most important differences and their implications.